Introduction to psychology - Wittig, Arno F.; Belkin, Gary S.; Wittig, Arno F. (New York : McGraw-Hill, 1990)
"An American BookWorks Corporation project." An introduction to the fundamentals of psychology including examples based on real-life situations or research literature. Key terms are defined in a glossary.
"A Schaum publication"--Cover.
"An American BookWorks Corporation project.".
Adaptation of: Schaum's outline of theory and problems of introduction to psychology. c1977.
Keywords: Psychology; Psychology